THE EFFECT OF VIRTUAL LITERATURE CIRCLE ON UNIVERSITY STUDENTS’ READING COMPREHENSION: A GENDER-BASED ANALYSIS - Mutiara Ayu; Zelvia Liska Afriani; Dyah Aminatun (The Journal of English Literacy Education: The Teaching and Learning of English as A Foreign Language, 2025)
This study investigates the effect of Virtual Literature Circles (VLCs) on the reading comprehension of university students, with a focus on gender-based differences. A mixed-methods approach was employed, involving a quasi-experimental design with pre-and post-tests, questionnaires, and interviews. The participants were divided into an experimental group (n = 30) and a control group (n = 30). The mean post-test score of the experimental group increased significantly from 65.23 (SD = 6.89) to 82.47 (SD = 5.32), while the control group showed a smaller improvement from 64.87 (SD = 7.14) to 70.23 (SD = 6.75). Independent sample t-tests confirmed a statistically significant difference in post-test scores between the two groups (p < 0.01). Gender-based analysis revealed that female students in the experimental group outperformed male students, with mean post-test scores of 84.15 (SD = 4.87) and 80.32 (SD = 5.64), respectively. Questionnaire and interview data indicated that female students reported higher levels of engagement, confidence, and perceived benefit from the VLCs. The findings suggest that VLCs are an effective and gender-responsive strategy for improving reading comprehension in higher education, particularly in virtual learning contexts.